Narative Review : Factors Related to the Occurrence of Diarrhea Among Under-Five Children - Resda Herliani; Riyan Ningsih; Akhmad Azmiardi (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Diarrhea in children under five years of age remains a significant global health crisis, particularly in developing countries, characterized by high morbidity and mortality rates. Although risk factors have been identified, geographic variations and the concentration of preventive interventions require a synthesis of updated evidence. Objective : This narrative review aims to provide a comprehensive update on the key determinants influencing diarrhea incidence in children aged 0-59 months. Research Methods/ Implementation Methods : The review was conducted on research articles published 2019-2024. The articles were retrieved from PubMed, Google Scholar, and ResearchGate databases, using keywords such as